2015
DOI: 10.5897/jece2014.0336
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal bioaccumulation and oxidative stress in Austroaeschna inermis (Dragon fly) of the Lagos Urban ecosystem

Abstract: Urban ecosystems are often characterized by the receipt of pollutants, especially heavy metals from diverse anthropogenic activities. To better understand the distribution of heavy metals (Cd, Cu, Pb, Mn and Zn), Austroaeschna inermis from five different sites (Unilag, Mile 12, Olushosun Dump site, Imoshe and Badagry) in Lagos, sediments from the respective sites were assessed. This was followed by assessment of lipid peroxidation product; Malondialdehyde (MDA) and antioxidative stress enzymes; superoxide dism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Research conducted in this study suggests that significant differences of environmental stress marker levels in c. erythrea are not a direct result of the site of insect collection but depend on differences in contamination and pollutants concentration in environment among studied sites. Similar results and finding were observed by Ihechiluru et al, (2015), who found insignificant difference between oxidative stress markers and the sites of collections, however there were strong positive or negative overall correlations between heavy metal concentrations in insects and respective oxidative stress markers.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Research conducted in this study suggests that significant differences of environmental stress marker levels in c. erythrea are not a direct result of the site of insect collection but depend on differences in contamination and pollutants concentration in environment among studied sites. Similar results and finding were observed by Ihechiluru et al, (2015), who found insignificant difference between oxidative stress markers and the sites of collections, however there were strong positive or negative overall correlations between heavy metal concentrations in insects and respective oxidative stress markers.…”
Section: Discussionsupporting
confidence: 90%
“…ROS are known to convert amino groups of proteins and thereby, change protein structure and function. The oxidative stress increased the number of modified carbonyl groups correlates with protein damage (Hermes-Lima, 2004). Also, ROS can cause fragmentation of the peptide chain, alteration of electrical charge of proteins, cross-linking of proteins, and oxidation of specific amino acids and therefore lead to increase susceptibility to proteolysis by degradation of specific proteases (Kelly and Mudway, 2003;Abdelfattah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herbivores have also elaborated protective mechanisms against the presence of toxic Zn concentrations in plant tissues. The ingestion of toxic metal concentrations induces ROS causing oxidative stress in herbivores (Ihechiluru et al, 2015). In order to survive, herbivores activate an effective antioxidant defense system (enzymes and non-enzyme compounds) that inhibits the metal-induced oxidative damage (Barata et al, 2005).…”
Section: Pathogens and Pests Evolve Mechanisms To Counteract Zinc-relmentioning
confidence: 99%